Penentuan Lokasi Tempat Pembuangan Sementara Sampah Menggunakan Metode Brown Gibson Berbasis Sistem Informasi Geografis - Sihotang, Dony Martinus; Tarus, Karen N.V; Widiastuti, Tiwuk (JSINBIS (Jurnal Sistem Informasi Bisnis), 2019)
The problem of waste has not been handled well, especially in cities, including the city of Kupang.Â  Placing the right location of the trash can be one of solutions to the waste problem. Â The purpose of this study is to combine decision support systems and geographic information systems to determine the location of TPS locations. There are two stages of analysis, the Brown Gibson method to determine which alternative is best for construction temporary landfill and the second analysis using the GIS approach to determine suitable point. The alternative is Neigborhoods (RT) in the Nefonaek, Kupang. The results showed that in the RT22, RT17, and RT18 which is outside the buffer area were selected as the best candidates for the new location of TPS. The system is tested in two ways, testing the blackbox using questionnaire on two respondents, and the accuracy that compares the results of the system and the results of expert. From the results of the blackbox testing, the percentage values for each GUI, Function, and information obtained were 94%, 92.5%, and 97.5%. And from Accuracy testing, obtained the value of accuracy on the first staff is 86.67% and for the second staff the accuracy value is 80%. From the two staffs obtained an average accuracy of 83.34%.